Lifting the veil on the "Untouchable": a study of Muslims living with HIV in Durban, South Africa - Shaik, Shabnam (Rhodes University, Faculty of Humanities, Department of Anthropology)
HIV and AIDS has been prominently studied, by both biomedical and social scientists, since the 1980s. Despite the extensive research that has emerged globally, Muslims have largely been absent in much of the discourse on HIV and AIDS. While the disease is said to be under control in many parts of the world, hidden populations pose a risk to increase in prevalence. Muslims living with HIV are one such hidden population and are only recently gaining representation in studies on HIV and AIDS. Quantitative studies reflect a sharp increase in HIV prevalence in countries with significant Muslim populations, however, more in-depth qualitative studies are needed to garner an understanding of the nature of the disease among Muslims. Muslims have a long history in South Africa, beginning with indentured slavery in Natal (now KwaZulu-Natal) in 1860. There are no specific HIV and AIDS prevention campaigns directed at Muslims in Durban, KwaZulu-Natal, South Africa. Muslims in Durban do not regard HIV is a significant concern for them due to religious doctrine, which they believe if followed will keep them safe from infection. My findings suggest that there is cause for concern over the spread of HIV and AIDS amongst Muslims in Durban. The hidden nature of the disease in the Muslim community has created challenges to curbing the spread of the disease due to the concealment of its presence and the marginalisation of Muslims living with HIV and AIDS. This study conceptualises the HIV and AIDS lived experience amongst Muslims in Durban, South Africa, and uncovers the social and cultural context of the disease. The qualitative study used life histories with ten Muslims living with HIV and semi-structured and unstructured interviews with ten caregivers, five health care professionals and two religious leaders to gain a detailed understanding of the lived experiences of Muslims in Durban. Through the lenses of Purity and Danger, Stigma and Spoilt Identity, and Social Death, this study found that religion [Islam] and its strong moral code influences understandings and perceptions of HIV and AIDS which, in turn affects diagnosis, treatment, care, social identity, and the social well-being of Muslims living with HIV who face stigma, discrimination, shame, and ostracisation from their own community. This study highlights the gaps in the literature on Muslims living with HIV and by providing insight into the lives of participants, the study draws attention to the plight of Muslims living with HIV and AIDS (MLWHIV) and encourages more qualitative studies to be conducted so that a multifaceted understanding of Muslims living with HIV can be created.
Keywords: AIDS (Disease) Religious aspects Islam; HIV infections Religious aspects Islam; AIDS (Disease) (Islamic law) -- South Africa; Muslims -- South Africa Durban; Traditional medicine -- South Africa; Integrative medicine